1983
DOI: 10.1017/s002185960003865x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulated day-degrees as a measure of physiological age and the relationships with growth and yield in early potato varieties

Abstract: SUMMARYData from nine experiments from 1973 to 1981 which examined the effects of physiological age on sprout and field growth of early potato varieties are reported. Length of longest sprout per tuber and all aspects of field growth were related to number of daydegrees > 4 °C experienced by the seed after onset of sprout growth (measured as the appearance of a 3 mm sprout). It is, therefore, suggested that this scale is an effective measure of physiological age. In Home Guard and Maris Bard, increasing age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 7 publications
2
37
0
1
Order By: Relevance
“…The long period between planting and emergence resulted from low temperatures after planting even if pre-sprouted seed starts to grow early when soil temperatures are around +6-8°C (O'Brien et al 1983). Nitrogen fertilizer application rate did not affect duration of this period, when the transfer of nutrients from the mother tuber greatly infl uences growth of the emerging plant.…”
Section: Mustonen L Yield Formation Of Early Potatoes During a Shormentioning
confidence: 99%
See 2 more Smart Citations
“…The long period between planting and emergence resulted from low temperatures after planting even if pre-sprouted seed starts to grow early when soil temperatures are around +6-8°C (O'Brien et al 1983). Nitrogen fertilizer application rate did not affect duration of this period, when the transfer of nutrients from the mother tuber greatly infl uences growth of the emerging plant.…”
Section: Mustonen L Yield Formation Of Early Potatoes During a Shormentioning
confidence: 99%
“…The numbers of main stems and number of tubers per hill were similar in all plots. When seed is presprouted early the numbers of stems and tubers per hill remain low and typical differences between genotypes are not evident (Varis 1973, O'Brien et al 1983. Also, within the broad range of commercial application rates the effect of nitrogen on the total number of stems and tubers is small.…”
Section: Mustonen L Yield Formation Of Early Potatoes During a Shormentioning
confidence: 99%
See 1 more Smart Citation
“…However, no analytical methods are available to predict the extent of physiological ageing. This reaction pattern has been gauged using the physiological age index (PAI) (Caldiz et al 2001), accumulated temperature sum (O'Brien et al 1983) and storage temperature sum (Struik and Wiersema 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, the onset of the different developmental stages and their duration can be quite different depending on the biological characteristics of the potato variety in question, the quality of the seed tuber, climatic and soil conditions, and the agrotechnical measures employed. Some authors report that physiologically older seed tubers allow for faster emergence than their younger counterparts (Iritani, 1968;O'Brien et al, 1983), while others have found no difference (Bus and Schepers, 1978). The experiments of Van Loon (1987), however, showed that physiologically older seed tubers emerge more slowly.…”
Section: Discussionmentioning
confidence: 99%